The role of personality and risk-taking on Tinder use. Issue 1 (2020) - Fowler, Samantha A.; Both, Lilly E.
Abstract: Tinder is a commonly used mobile dating application. Its widespread use and reputation have led many researchers to investigate individual differences and motivations for using the app. In the present study, we investigated personality, risk-taking, and loneliness in relation to Tinder use. A total of 267 individuals participated in this survey study. Questionnaires that assessed demographics, personality, loneliness, risk-taking and Tinder use were administered either online or in paper form. The results indicated that the most common reasons for using Tinder included entertainment and to begin a relationship. As well, many participants reported taking safety precautions before meeting someone in person that they had met on Tinder. The results of a sequential logistic regression revealed that Tinder use was predicted by relationship status (i.e., not in a relationship), personality traits (higher extraversion and lower conscientiousness scores) and risk-taking. Specifically, people who use Tinder are more likely to be single, outgoing, spontaneous, fun-loving risk-takers. However, these variables only explained approximately a quarter of the variance in Tinder use. Thus, more research is needed to understand Tinder use from a psychological perspective.